2013
DOI: 10.1371/journal.pone.0077128
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Fermentation of NUTRIOSE® FB06, a Wheat Dextrin Soluble Fibre, in a Continuous Culture Human Colonic Model System

Abstract: Wheat dextrin soluble fibre may have metabolic and health benefits, potentially acting via mechanisms governed by the selective modulation of the human gut microbiota. Our aim was to examine the impact of wheat dextrin on the composition and metabolic activity of the gut microbiota. We used a validated in vitro three-stage continuous culture human colonic model (gut model) system comprised of vessels simulating anatomical regions of the human colon. To mimic human ingestion, 7 g of wheat dextrin (NUTRIOSE® FB0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 58 publications
0
20
0
Order By: Relevance
“…Pectin is a plant polysaccharide consisting of α-D-galacturonic acid and is a component of the primary cell walls of terrestrial plants [ 33 ]. Dextrins are produced in the human body as a result of enzymatic digestion of starch [ 34 ]. The KEGG pathway in the Supplementary S1 File showed that the enzymes produced for dextrin and pectin utilization were present in the CR0044 genome under the starch and sucrose metabolism ( S1 File ).…”
Section: Resultsmentioning
confidence: 99%
“…Pectin is a plant polysaccharide consisting of α-D-galacturonic acid and is a component of the primary cell walls of terrestrial plants [ 33 ]. Dextrins are produced in the human body as a result of enzymatic digestion of starch [ 34 ]. The KEGG pathway in the Supplementary S1 File showed that the enzymes produced for dextrin and pectin utilization were present in the CR0044 genome under the starch and sucrose metabolism ( S1 File ).…”
Section: Resultsmentioning
confidence: 99%
“…The reduced capacity of the microbiota to ferment dietary carbohydrates could readily be examined using methodologies ex vivo by, for example, adapting faeces of patients with UC to models of gut microbiota 35. Examination of individual or collective bacteria populations has not been validated as a method of predicting fermentative capacity.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo studies conducted using inulin and various oligofructoses have shown an inhibition of animal and human pathogenic bacterial groups and increase in bifidobacteria and SCFAs (Saad et al, 2013 ). Several recent studies have also employed in vitro models to compare the effects of introducing pectin, inulin (Johnson et al, 2015 ; Chung et al, 2016 ), and wheat dextrin (Hobden et al, 2013 ) on the gut microbiota. These studies have demonstrated the potential of the fiber additions to enrich specific members of the genus Bacteroides and phylum Firmicutes (Hobden et al, 2013 ; Johnson et al, 2015 ; Chung et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%